Physiological and Biochemical Responses of ‘Burlat’ Sweet Cherry to Pre-Harvest Foliar Application of Calcium and Seaweed Extracts - Sandra Pereira; Vânia Silva; Francisco Guedes; Fernando Raimundo; João Ricardo Sousa; Ana Paula Silva; Berta Gonçalves (Horticulturae)
Sweet cherry (Prunus avium L.) is a highly valued fruit, and optimal nutrient management is crucial for enhancing yield and fruit quality. However, the over-application of chemical fertilizers in cherry cultivation leads to environmental issues such as soil degradation and nutrient runoff. To address this, foliar application, a more targeted and eco-friendly fertilization method, presents a promising alternative. This study evaluates the effects of pre-harvest foliar application of calcium (Ca) (150 and 300 g hL−1) and seaweed extracts (75 and 150 mL hL−1), both individually and in combination, on the physiological and biochemical responses of ‘Burlat’ sweet cherry trees. Key physiological parameters, including plant water status, photosynthetic performance, and leaf metabolites, were analyzed. Results show that trees treated with seaweed extracts or with combined Ca and seaweed application had improved water status, higher sugar, starch, and protein content, as well as enhanced antioxidant activity and phenolic content compared to those treated solely with calcium. However, the combined treatment did not significantly enhance overall tree performance compared to individual applications. This study highlights the potential of seaweed-based biostimulants in sustainable cherry production.